Human Rights Education Based on Maqāṣid al-Sharī‘ah in the Curriculum and Culture of Islamic Boarding Schools - Feri Indra Irawan; Hilman Rasyid; Dul Wahid; Mohamad Erihadiana (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This study examines the implementation of maqāṣid asy-syarī‘ah values in the human rights education model at Pesantren Persis 67 Benda, Tasikmalaya, focusing on curriculum and institutional culture. Maqāṣid asy-syarī‘ah, which includes the protection of religion, life, intellect, lineage, and property, aligns with universal human rights principles. Using a qualitative case study approach, data were collected through document analysis, observation, and interviews with teachers and administrators. The findings reveal systematic internalization of maqāṣid values through an integrative curriculum and institutional practices. Critical thinking training, moral development, and social-dakwah programs exemplify the Islamic-based implementation of human rights. Challenges include limited student participation in decision-making and tensions between discipline and individual freedom. The study concludes that a maqāṣid-based educational model offers a philosophical and operational foundation for developing a contextual, Islamic approach to human rights that promotes humanistic character formation.